INFLUENCE OF WASTEWATER TYPE AND ELECTRODE SPACING FOR MICROBIAL FUEL CELL PERFORMANCE - ZEPHANIAH SURYAGA (NIM : 23015016), KENNY
The common problems in this world are energy crisis and increasing waste production. Solutions of those problems are energy saving, energy development and utilization to change fossil fuel, one of the example is microbial fuel cell (MFC). Microbial fuel cell is a device that can generate electricity directly fraom conversion of chemical energy that contained in organic substances with microorganism help. Beside of that MFC can als be used as effective wastewater treatment technology In this research, the influence of wastewater type and electrode spacing against the power generated by MFC are studied. The configuration of microbial fuel cell in this research is two-chamber MFC. Anode chamber is filled by wastewater and inoculum at anaerobic condition. The inoculum is isolated from cowÃ‚Â’s feces and inoculated in a liquid medium. The KMnO4 0,02 M and phosphat buffer pH 7 solution are used as a catholyte in cathode chamber at aerobic conditions. Carbon sheet wothout catalyst is used as electrode and Nafion 212 is used as proton exchange membrane. There are two wastewater used in this research and they are tofu wastewater and palm oil mill effluent (POME). There are four variation of electrode spacing which are used in this research. First is adhere together (ST), which both anode and cathode are adhere together and the electrodes are seperated by Nafion membrane, the second is seperated electrode (SP), which each anode and cathode is seperated 1 cm from membrane, the third is adhered anode (AT), which anode adhere with membrane and have a 1 cm distance from cathode and the last variation is adhered cathode (KT), which cathode adhere with membrane and have 1 cm distance from anode. Overall, from wastewater type variation, POME produced Open Circuit Voltage (OCV) and power density higher than tofu wastewater. From electrode spacing variation, the highest OCV is obtained at MFC with adhered cathode system (KT) and the highest power density is obtained at MFC with adhere together electrode (ST). In this research, maximum OCV is 880 milivolts obtained at POME-KT run and maximum power density is 25,22 mW/m2 and current density is 52,8 mA/m2 obtained at POME-ST run. From Electrochemical Impendance Spectroscopy (EIS) test, we can see the resistance values are very high in this MFC research and they are dominated with charge transfer resistance. The COD removal are about 42-53% for tofu wastewater and 57-66% for POME.